Connecting Library with APEX Community - Jan Mohamad, Radia Banu; Mohd Napiah, Mohd Kamal; Ibrahim, Intan Haryati; Ismail, Mohd Ikhwan; Wan Jan, Noor Azlinda; A. Basheer Ahamadhu, Ameer Sultan; Ibrahim, Asma Wati (2013)
Hamzah Sendut Library as an APEX university library has taken a more proactive approach to rebrand promotional and outreach programs. A more creative, unique and inno-vative style have been used to ensure that the library's mis-sion in reaching out to the users is accomplished. ‘Skuad Pelanggan’ was formed to increase the effectiveness of library’s engagement with customers. The ultimate goal is to reach out to customers, increase the usage of library facilities, improving the relevance of the existence of the library in the campus community and provide additional value to the library users. Important aspects emphasized in the program include teaching and learning supports, with the focus on research and consultation. Efforts conducted through myPHS programs, exhibitions, and virtual market-ing have established positive impacts and realization of library’s relevance by the campus community.